Digital dashboards visualizing public health data: a systematic review - Schulze, Annett; Brand, Fabian; Geppert, Johanna; Böl, Gaby-Fleur (Frontiers in Public Health, 2023)
Public health is not only threatened by diseases, pandemics, or epidemics. It is also challenged by deficits in the communication of health information. The current COVID-19 pandemic demonstrates that impressively. One way to deliver scientific data such as epidemiological findings and forecasts on disease spread are dashboards. Considering the current relevance of dashboards for public risk and crisis communication, this study provides results of a systematic review of peer-reviewed journal articles and conference proceedings (n=65) assessing the state of research on dashboards in the context of public health risks and diseases. Firstly, the study assesses public health issues covered by dashboards as well as the respective data sources, the information visualized by dashboards and different graphical representations used to visualize data or indicators in dashboards. Secondly, the literature review sheds light on public health challenges as well as objectives addressed by the respective dashboards. Thirdly, the review analyses the extent to which user needs play a role in the development and evaluation of a dashboard. Finally, and through a methodological informed differentiation between descriptive studies and user studies, the review also assesses the quality of included user studies (n=18) through the use of the Mixed Methods Appraisal Tool (MMAT). Overall, the literature review shows that studies that do not only describe the construction of a specific dashboard, but also evaluate its content in terms of different risk communication models or constructs (e.g. risk perception or health literacy) are comparatively rare. Furthermore, while some of the studies evaluate usability and corresponding metrics from the perspective of potential users, many of the studies are limited to a purely functionalistic evaluation of the dashboard by the respective development teams. These results suggest that applied research on public health intervention tools like dashboards would gain in complexity through a theory-based integration of user-specific risk information needs.